Begrepet kunstnerisk kvalitet i den norske kulturskolens rammeplan «Mangfold og fordypning», utfordret med et sideblikk til finsk «grundundervisning i konst» - Anna-Lena Østern (Cappelen Damm Akademisk NOASP, 2017)
The aim of this article is to contribute to increased knowledge about how «artistic quality» is described and understood in the Norwegian framework curriculum for music and performing art schools, «Cultural diversity and deeper understanding», from 2016. This is effected through a juxtaposition of the Norwegian framework with sketches of a Finnish framework for basic arts education concerning value foundation, aims and view on learning. The document analysis is carried out as a critical discourse analysis. As a frame of understanding the concept art is read in the light of Bourdieu and Ranciére, while the concept quality is read in the light of different contemporary quality understandings, with some concluding suggestions regarding alternative concepts like meaning making and interpretive community. The main finding in the analysis is that the concept «artistic quality» is difficult to define in the Norwegian framework, and that the concept not is in use in the Finnish framework sketch. The main lines in formulations about value foundation coincide in the plans from both countries. The challenge from the Finnish sketches is in this study how the view of present and future times is mirrored in formulations about what is meaningful and valuable in the light of aesthetic, ethical and ecological considerations.